Traditional Greetings Used in the Bathhouse - Jasiūnaitė, Birutė (Kalbotyra, 2000)
The present work makes an attempt to analyse Lithuanian traditional verbal forms of bathing etiquette. The analysis showed that such stereotypes are closely related to greetings used by working, drinking and eating people. Some facts of Lithuanian mythical vocabulary bear a close resemblance to Russian: pirtìnis ‘банный, банник’, dirìkas ‘обдериха’. One of traditional formulas became the title of this article.